Critical Appraisal of Emergency Medicine Educational Research: The Best Publications of 2015. (17th October 2017) - Heitz, Corey R.; Coates, Wendy; Farrell, Susan E.; Fisher, Jonathan; Juve, Amy Miller; Yarris, Lalena M.
Abstract: Objective: The objectives were to critically appraise the medical education research literature of 2015 and review the highest‐quality quantitative and qualitative examples. Methods: A total of 434 emergency medicine (EM)‐related articles were discovered upon a search of ERIC, PsychINFO, PubMED, and SCOPUS. These were both quantitative and qualitative in nature. All were screened by two of the authors using previously published exclusion criteria, and the remaining were appraised by all authors using a previously published scoring system. The highest scoring articles were then reviewed. Results: Sixty‐one manuscripts were scored, and 10 quantitative and two qualitative papers were the highest scoring and are reviewed and summarized in this article. Conclusions: This installment in this critical appraisal series reviews 12 of the highest‐quality EM‐related medical education research manuscripts published in 2015.